Triticum aestivum L. subsp. aestivum CWI 82588 ... - GLIS Of The ITPGRFA (Centro Internacional de Mejoramiento de Maíz y Trigo, 2017)
Plant Genetic Resource. Taxonomy: Triticum aestivum L. subsp. aestivum Common name(s): Wheat Other names: TAIGA Conserved by: Centro Internacional de Mejoramiento de Maíz y Trigo (CIMMYT), Mexico Local sample unique identifier: CWI 82588 Method of creation: Acquisition Date: 2011-01-01 Other identifiers: n/a,CWI82588, n/a,TAIGA Historical: No Biological status: Breeder's line MLS status: Included ...